Use of bio-physical indicators to map and characterize coping strategies of households to Rift Valley fever outbreaks in Ijara District - Kiplimo, Jusper Ronoh; Notenbaert, An Maria Omer; Bett, Bernard K.; Waithaka, H.E. (2014)
Extended and above normal rainfall across (semi-) arid Africa after a warm phase of El Niño creates conditions favorable for outbreak of Rift Valley Fever (RVF); a vector borne disease. There have been two major epizootics in the Horn of Africa in 1997/98 and 2006/07 that had the highest mortality to both humans and livestock. Our study, at Ijara District- Kenya, characterizes coping strategies used by communities in high and low risk areas to make themselves less vulnerable to effects of adverse climate variability and in consequent RVF outbreaks. RVF outbreaks resolved to division level werecollated to bio-physical factors that were significantly associated with the outbreaks. Geostatistical analyses were used to identify RVF risk areas. At selected risk areas, focus group discussions (FGDs) involving the local communities, community health workers, and veterinary officers were used to characterize coping strategies that were employed in recent RVF outbreak. Solonetz, luvisols and vertisols and areas below 1000m were significant. Low areas, fairly flat with a 0 – 15% slope rise having these soil types have higher risk compared to the other areas. The low and high RVF risk areas were approximately split halfway across district, northwards and southwards respectively. From the FGDs, actions taken by communities at high risk areas were strategic while those at low risk areas used reactive, ad hoc coping strategies. Communities at high risk areas would cope better to adverse climate variability and extended disease burden compared to those at low risk areas who lack knowledge of some of those strategies. More needs to be done to understand climate variability, disease ecology of RVF, community awareness and facilitation as there are at times the whole district is affected by the RVF.